Improving Human-Lion Conflict Research Through Interdisciplinarity - Beck, Jacalyn M.; Lopez, Maria Claudia; Mudumba, Tutilo; Montgomery, Robert A. (Frontiers in Ecology and Evolution, 2019)
Wicked socio-ecological problems are inherently complex and require an interdisciplinary approach to mitigate. Here, we investigated the many drivers of human-lion conflict in East Africa and present a novel conceptual model illustrating the intricate interactions within and between the five main dimensions of conflict. We highlight the importance of broadening research efforts to include these multiple dimensions at all stages of the research process as well as to incorporate higher levels of diversity into research teams. We offer examples and recommendations on how to approach human-lion conflict from a more interdisciplinary perspective. However, challenges exist and will continue to arise as diverse interdisciplinary teams form. We address several main barriers to interdisciplinarity and encourage researchers and institutions to support a team science approach to solving wicked problems like human-lion conflict.